Pengaruh Literasi Digital terhadap Perilaku Kerja Inovatif di Perusahaan BPRS Amanah Rabbaniah - Fransisca, Fasya; Caroline, Angela; Kornarius, Yoke Pribadi; Gunawan, Theresia; Gunawan, Agus (MES Bogor, 2024)
Digital transformation has put tremendous pressure on every company that requires its workers to be able to innovate in using technology. This study will show the extent to which digital literacy affects innovative work behavior at the BPRS Amanah Rabbaniah company. The operation of the banking industry relies heavily on digital technology, but the innovation gap is limited due to banking regulations from the government. This study aims to find out the extent to which employee’s innovative work behavior can be influenced by employee digital literacy. This research uses a survey method, where data collection uses a digital questionnaire distributed to 50 employees. The data was processed using a simple linear regression test to prove the effect of digital literacy on innovative work behavior. Furthermore, the data is presented in a frequency distribution table to find the tendency of respondents' answers. The results of data processing show that digital literacy affects innovative work behavior. All indicators in digital literacy have a good category, while in IWB there are 2 indicators that have a sufficient category. The findings of this study indicate that in banking companies the workflow is fully supervised by OJK & existing BI regulations, so that employees get job instructions directly from superiors or leaders where employees cannot simply provide innovative ideas at work but do not rule out the possibility for workers to continue to innovate in the use of digital technology at their work.